The Evaluation of Liquidity and Capital Structure of Manufacturing Firms in Nigeria - Evinemi, Elijah Adeiza; Emengini, Steve Emeka (International Journal of Economics and Financial Issues, 2024)
Firms’ choices regarding their capital structure influence their net cost or value. Firm characteristics such as firm size, liquidity, growth opportunities, asset tangibility, non-debt tax shield and cost of equity are specific traits of firms. This study investigates the effect of firm liquidity on capital structure of manufacturing firms in Nigeria. Annual data was obtained from reports of thirty-one (35) manufacturing firms covering the period 2007-2021. The effects of liquidity on capital structure were examined using the panel Fixed/Random effect methods. The summary statistics, correlation analysis, slope heterogeneity and cross-sectional dependence were conducted as pre-estimation procedures. The study employed debt-to-equity and debt-to-asset ratios to capture capital structure, while cash conversion cycle in days was used to measure liquidity. The findings show that liquidity has negative significant relationship in explaining the debt-to-asset of manufacturing firms and no significant effect in explaining the debt-to-equity of manufacturing firms in Nigeria. The study recommends that manufacturing firms embrace innovation as a way of increasing the efficiency of the total assets. Also, manufacturing firms should formulate main policies, which support the implementation of positive cash flow.